Subsídios para a elaboração do diagnóstico do sistema de drenagem do Campus da UFMT, Cuiabá, MT - Jesus, Valéria Shirley Orth de (2017)
The management of a Watershed can bump into criteria that hinder their achievement as: topographic survey and determination of land use and occupation. The Geographic Information System (GIS), has become a tool that assists in the determination of these parameters may also be used as a factor of visual management that demonstrates the potential risk areas. The overall goal is to give subsidies for the development of diagnosis of the drainage system in order to support the implementation of the Plan of drainage to compose the plan for the sustainable management of the UFMT. The methodology used is based on the realization of maps: slope, level curves, distances from water supply network and land use and occupation with use of GIS system. The area of this study is located in the central region of Brazil, in Cuiaba, the capital of the state of Mato Grosso, in the hydrographic basin of the stream of the Barbado. The maps of slope, slopes, altitude, distance from the water supply network, were obtained from satellite images of the numeric model of the terrain (NTM), this numerical model, as Camera, Monteiro and Davis (2004) is the representation of mathematical a space phenomenon that occurs on the surface of the earth. This file has the format array with a resolution of 30 meters. Already the use and occupation of the land was carried out with the classification of satellite image of Landsat 5 TM, 24.08.2016 with the geoprocessing image on the system Acronyms Datum 2000. In conclusion, the basin have a capacity draining regular, but presents a form that promotes the incidence of flooding. However, today there occur cases of flooding in the stream in the region considered medium-haul flights as a result of obstructions in runoff by road network deployed and by lack of maintenance of the galleries rainwater drainage system. With the deployment of the work of the viaduct, this prevents the flow naturally causing an accumulation of water at the outlet of the high and adjacent areas.